Recreational Physical Activity Ameliorates Some of the Negative Impact of Major Depression on Health-Related Quality of Life - Patten, Scott B.; Williams, Jeanne V.; Lavorato, Dina H.; Bulloch, Andrew G. (Frontiers in Psychiatry, 2013)
Background: Major depressive episodes (MDEs) have a negative effect on health-related quality of life (HRQoL). The objective of this study was to determine whether recreational physical activity can ameliorate some of this negative impact. Methods: The data source for the study was the Canadian National Population Health Survey (NPHS). The NPHS is a longitudinal study that has collected data from a representative cohort of 15,254 community residents. Sixteen years of follow-up data are available. The NPHS included: an instrument to assess MDE (the Composite International Diagnostic Interview Short Form for Major Depression), an inventory of recreational activities (each associated with hours of participation and estimated metabolic expenditures) and a HRQoL instrument (the Health Utility Index, Mark 3 or HUI3). Proportional hazard and linear regression models were used in this study to determine whether MDE-related declines in HRQoL were lessened by participation in an active recreational lifestyle. Results: Consistent with expectation, major depression was associated with a significant decline in HRQoL over time. While no statistical interactions were observed, the risk of diminished HRQoL in association with MDE was reduced by physical activity. In a proportional hazards model, the hazard ratio for transition to poor HRQoL was 0.7 (95% CI: 0.6 – 0.8, p < 0.0001). In linear regression models, physical activity was significantly associated with more positive HRQoL (β = 0.019, 95% CI 0.004 to – 0.034, p =0.02). Conclusions: Recreational physical activity appears to ameliorate some of the decline in HRQoL seen in association with MDE. Physical activity may be an effective tertiary preventive strategy for this condition.